Acanthostyles (Asteraceae, Eupatorieae): a revision with a multivariate analysis - Grossi, Mariana Andrea (2011)
The Neotropical genus Acanthostyles R.M.King & H.Rob. (Asteraceae, Eupatorieae) occurs from northern Argentina up to northern Patagonia, southern Brazil, central and southern Bolivia, and Uruguay. Different taxonomic treatments have suggested that Acanthostyles might include two species (A. buniifolius (Hook.& Arn.) R.M.King & H.Rob. and A. saucechicoensis (Hieron.) R.M.King & H.Rob.), or even only a single, highly variable, species. Therefore, a detailed morphological study and a taxonomic revision of Acanthostyles were carried out. A principal component analysis of 73 specimens, representing the morphological variability and geographic distribution of Acanthostyles, was conducted to test the validity of these taxa. Results showed that the morphological variation of A. saucechicoensis is included within the infraspecific variation of A. buniifolius. No clearly separated groups were revealed by the principal component analysis. We, therefore, propose that A. saucechicoensis is treated as a synonym of A. buniifolius, and thus Acanthostyles becomes a single, highly variable species throughout its range.